116k views
4 votes
Using substitution what is the value for x for the equations 2x+y=-3 and y=4x+6​

1 Answer

2 votes

Answer:


x = (-3)/(2)

Step-by-step explanation:

Given

2x + y = -3

y = 4x + 6

Required

Find the value of x

2x + y = -3 --- Equation 1

y = 4x + 6 --- Equation 2

Substitute 4x + 6 for y in equation 1.

So, equation 1 becomes


2x + 4x + 6 = -3


6x + 6 = -3

Subtract 6 from both sides


6x + 6 - 6 = -3 - 6


6x = -9

Divide both sides by 6


(6x)/(6) = (-9)/(6)


x = (-9)/(6)

Simplify fraction


x = (-3)/(2)

Hence, the value of x is
x = (-3)/(2)

User Artyom Shalkhakov
by
5.4k points